2005
DOI: 10.1186/1471-2474-6-35
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of upright posture measurements in primary school children

Abstract: Background: Correct upright posture is considered to be a measure of good musculoskeletal health. Little is known about the usual variability of children's upright standing posture. The aim of this study was to assess differences between repeated measures of upright posture in a group of primary school children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
107
1
28

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(142 citation statements)
references
References 13 publications
6
107
1
28
Order By: Relevance
“…However, in our study comparing balance in boys and girls born at term and preterm, no difference was found in the ability to maintain balance control in the conditions of dynamic and static equilibrium according to gender. Our research confirms the results of McEvoy and Grimmer [25], who found that in children aged 5-12, there is no relationship between gender and the extent of angular movement when standing. On the other hand, there are studies showing that sexual dimorphism affects the process of controlling body posture mainly during puberty [6,13,19,22,26,28,38].…”
Section: Discussionsupporting
confidence: 82%
“…However, in our study comparing balance in boys and girls born at term and preterm, no difference was found in the ability to maintain balance control in the conditions of dynamic and static equilibrium according to gender. Our research confirms the results of McEvoy and Grimmer [25], who found that in children aged 5-12, there is no relationship between gender and the extent of angular movement when standing. On the other hand, there are studies showing that sexual dimorphism affects the process of controlling body posture mainly during puberty [6,13,19,22,26,28,38].…”
Section: Discussionsupporting
confidence: 82%
“…McEvoy & Grimmer 16 have pointed out that the posture of children changes from 7 to 12 years as the child adapts to his or her new bodily proportions. Penha et al 17 analyzed the body posture of healthy schoolchildren aged from 7 to 10 years and found a high rate of altered postures.…”
Section: Discussionmentioning
confidence: 99%
“…After completing the evaluation form, participants remained seated in an upright position and were asked the following placements: anteriorization and posteriorization from the head; flexion and extension of the cervical spine. The evaluations were performed in the sitting position for it being often harmful to the spine, particularly the cervical spine, even more than the standing position, and because the work position of many professionals that work with computers and/or in worktables 13,25 . Anatomical points were marked on the skin with circular markers stickers with 9 mm diameter from the Pimaco brand.…”
Section: Methodsmentioning
confidence: 99%
“…For that, it is necessary to have a standardization of the environment and of the camera`s position for the correct recording without image distortion and good distinctness 11,12 . One of the photographical methods for postural assessment with photographic images is computerized photogrammetry 13 . This method provides measurements of body angles from photographs, which allows a quantified postural assessment 2,6,14,15 .…”
Section: Introductionmentioning
confidence: 99%